1999
DOI: 10.1016/s0022-5347(05)68156-6
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Alterations in Nitric Oxide Levels in the Paraventricular Nucleus on Copulatory Behavior and Reflexive Erections in Male Rats

Abstract: Altered NO levels in the PVN affected the frequency of reflexive erections, but not the mount rate. These studies contrast with previous observations of the effects of altered NO levels in the MPOA, and support the hypothesis that physiological specificity in the actions of NO on discrete brain nuclei may have important implications to erectile physiology and dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 18 publications
1
32
0
Order By: Relevance
“…Thus, although NO appears to be important for the initial acquisition of copulatory behavior, it may not be an absolute requirement for its maintenance. However, even sexually experienced rats in this and other studies have shown sexual deficits with systemically (Benelli et al, 1995;Bialy et al, 1996;Hull et al, 1994) or centrally (Melis et al, 1998;Sato et al, 1998Sato et al, , 1999 administered NOS inhibitors.…”
Section: Discussionmentioning
confidence: 46%
“…Thus, although NO appears to be important for the initial acquisition of copulatory behavior, it may not be an absolute requirement for its maintenance. However, even sexually experienced rats in this and other studies have shown sexual deficits with systemically (Benelli et al, 1995;Bialy et al, 1996;Hull et al, 1994) or centrally (Melis et al, 1998;Sato et al, 1998Sato et al, , 1999 administered NOS inhibitors.…”
Section: Discussionmentioning
confidence: 46%
“…Direct measurements of NO in the MPOA showed NO release associated with copulatory behavior. Local administration of a NOS inhibitor decreased NO release and copulatory behavior (Sato et al, 1998(Sato et al, , 1999. NO production increased in the PVN during noncontact erection and copulation .…”
Section: Nitric Oxidementioning
confidence: 97%
“…16,34 ± 37 NO may act in several discrete brain regions, eg in the medial preoptic area 36,37 as well as in the paraventricular nucleus. 9,16 Injection of NOS inhibitors intracerebroventricularly or in the paraventricular nucleus prevented penile erectile responses induced by dopamine agonists, oxytocin, and NMDA in rats.…”
Section: Opioid Peptidesmentioning
confidence: 99%